CHANGES IN LEADERSHIP BEHAVIORS OF ELEMENTARY SCHOOL CHILDREN IN CAMP GROUPS - KURAMOTO, MITSUE (Jikken shakai shinrigaku kenkyū, 1981)
The purpose of this study was to examine the changes of leadership behavior through a fiveday camp experiences and the effect of camping upon the leadership behavior in the school. The subjects were 58 fifth graders and 41 sixth graders, who perticipated in the camp held in July 1979. For the present study, 1) The Leadership Behavior Rating Scale, 2) The Sociometric Test, 3) The Achievement Motivation Rating Scale, 4) The Level of Aspiration Inventory, 5) The Satisfaction Rating Scale and 6) The Y-G Personality Inventory were administered. Based on the findings, it was concluded that: 1) Under the situations that was difficult to achieve group objectives without members' cooperation, camper leadership behavior tended to increase in comparison with ordinaly camp situations. 2) Significant positive changes in leadership behavior through camp experiences were found for children in school life (P<. 001). 3) With regard to group effectiveness, Mixed Groups were highest and High Groups came second, and Low Groups were lowest of experimental survival groups. 4) Group members who took leadership roles had high achievement motivation (P<. 05) and high level of aspiration (P<. 05), tended to have high popularity (P<. 06), and showed active and extrovert attributes (P<. 05). The results of this study indicate that the camp program, which is planned to necessiate group cooperation, contributes to the development of childrens' leadership behavior.